Magnetic ferroferric oxide biochar, preparation method thereof and application of magnetic ferroferric oxide biochar as catalyst in degradation of organic pollutants
By preparing magnetic ferrotetraoxide biochar as a catalyst, the problem of low efficiency of biochar activated peracetic acid is solved, and efficient and environmentally friendly organic pollutant degradation and multiple reuse are achieved. It is suitable for a variety of water bodies and pH conditions. .
Patent Information
- Application Number
- CN202411571697.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, biochar activated peracetic acid has low activation efficiency and poor reusability, making it difficult to effectively degrade organic pollutants.
Using magnetic ferrotetraoxide biochar as a catalyst, nitrogen-containing peel biochar is prepared by calcining the peel powder, and solvothermal reaction with iron salt and sodium acetate to form magnetic ferrotetraoxide biochar with iron tetraoxide supported. , used to catalyze peracetic acid to degrade organic pollutants.
It has achieved multiple reuses of efficient degradation of organic pollutants, maintained a catalytic efficiency of more than 80%, and showed good applicability in different water bodies and pH ranges, reducing catalyst costs and environmental pollution risks.
Smart Images

Figure CN119186623A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic pollutant wastewater treatment, and specifically relates to a magnetic ferroferric oxide biochar and a preparation method thereof and application of the biochar as a catalyst in degrading organic pollutants. Background Art
[0002] Peracetic acid (PAA, CH3C(=O)OOH) is a broad-spectrum, highly efficient, environmentally friendly disinfectant. Due to its efficiency in organic matter degradation and low cost, it has become a hot technology for the removal of new pollutants in water treatment. PAA is a colorless, transparent liquid that is weakly acidic, volatile, and has a strong pungent acetic acid odor. It does not leave any residue in the environment, so it is considered a green ecological disinfectant.
[0003] In the field of water treatment, PAA-based advanced oxidation technology has attracted widespread attention. PAA can be activated in a variety of ways to improve its oxidation capacity and effectively remove organic pollutants in water.
[0004] As a renewable carbonaceous material, biochar shows great potential in water treatment due to its unique physical and chemical properties. Biochar is usually prepared by pyrolysis of biomass under anaerobic conditions and has a high specific surface area, rich pore structure and adjustable surface functional groups. These properties enable biochar to effectively adsorb and remove a variety of pollutants, including heavy metals and organic pollutants, in water treatment. Biochar is prepared from a wide range of raw materials, is low-cost and environmentally friendly, and is considered to be a sustainable water treatment material. However, the use of biochar alone to activate PAA has defects such as low activation efficiency and poor reusability. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a magnetic ferroferric oxide biochar and its preparation method and use as a catalyst in the degradation of organic pollutants. The magnetic ferroferric oxide biochar can not only be used as a catalyst to effectively catalyze the oxidant to degrade organic pollutants, but can also be recycled, is environmentally friendly, and can maintain high catalytic efficiency through repeated use.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing magnetic ferroferric oxide biochar, comprising the following steps:
[0008] After calcining the peel powder in a nitrogen protective atmosphere, the peel powder is crushed and sieved in sequence to obtain nitrogen-containing peel biochar;
[0009] The nitrogen-containing peel biochar, organic solvent, iron salt and sodium acetate are mixed and subjected to a solvothermal reaction to obtain magnetic ferrosoferric oxide biochar.
[0010] Preferably, the mass ratio of the nitrogen-containing peel biochar to the iron salt is 1:3-5; the mass ratio of the nitrogen-containing peel biochar to sodium acetate is 1:3-5.
[0011] Preferably, the temperature of the solvent thermal reaction is 150-300° C., and the insulation time is 6-12 hours.
[0012] The present invention also provides magnetic ferroferric oxide biochar prepared by the preparation method described in the above technical scheme, comprising nitrogen-containing peel biochar and ferroferric oxide loaded on the surface and pores of the nitrogen-containing peel biochar; the mass percentage of ferroferric oxide in the magnetic ferroferric oxide biochar is 18-30%, the mass percentage of nitrogen-containing peel biochar is 65-81%, and the mass percentage of nitrogen element is 1-5%; the specific surface area of the magnetic ferroferric oxide biochar is 20-40m 2 / g, pore volume is 0.0030~0.0040cm 3 / g, pore size is 2~30nm.
[0013] The present invention also provides the use of the magnetic ferroferric oxide biochar described in the above technical solution as a catalyst in degrading organic pollutants.
[0014] The present invention also provides a method for degrading organic pollutants, comprising the following steps:
[0015] A medium containing organic pollutants, peracetic acid and a catalyst are mixed to perform degradation treatment;
[0016] The catalyst is the magnetic ferroferric oxide biochar as described in claim 4.
[0017] Preferably, the organic pollutant is one or more of tetracycline, bisphenol A, methylene blue, sulfamethoxazole, diclofenac and ofloxacin.
[0018] Preferably, the concentration of organic pollutants in the medium containing organic pollutants is 5 to 20 mg / L.
[0019] Preferably, the dosage of the catalyst in the medium containing organic pollutants is 0.02 to 0.10 g / L.
[0020] Preferably, the concentration of the peracetic acid in the medium containing organic pollutants is 25-200 μmol / L.
[0021] The invention provides a method for preparing magnetic ferroferric oxide biochar, comprising the following steps: calcining peel powder in nitrogen protective gas, then crushing and screening in sequence to obtain nitrogen-containing peel biochar; mixing the nitrogen-containing peel biochar, an organic solvent, an iron salt and sodium acetate, and performing a solvothermal reaction to obtain magnetic ferroferric oxide biochar. The invention combines ferroferric oxide with biochar with strong magnetism to increase the active sites of the catalytic reaction, so as to improve the catalytic performance of the magnetic ferroferric oxide biochar, and can also recover the catalyst through an external magnetic field. At the same time, biochar with a large specific surface area can effectively reduce the agglomeration of magnetic metals. The surface of the magnetic ferroferric oxide biochar contains rich ferroferric oxide, and iron ions can promote the production of free radicals (acetoxy radicals and acetylperoxy radicals) by peracetic acid, thereby improving the removal effect of organic pollutants. The introduction of ferroferric oxide not only enhances the catalytic activity of biochar, but also broadens its application range in water treatment. Moreover, biochar loaded with ferroferric oxide can also effectively reduce the leaching of Fe ions to prevent secondary pollution to the environment. Therefore, the present invention uses magnetic ferroferric oxide biochar as a catalyst to catalyze the degradation of organic pollutants by peracetic acid. Compared with existing carbon materials, it is recyclable, environmentally friendly, has higher system stability, and can maintain high catalytic efficiency through repeated use.
[0022] The experimental results confirm that when the magnetic ferroferric oxide biochar catalyst provided by the present invention is used to activate peracetic acid to degrade tetracycline wastewater, the magnetic ferroferric oxide biochar catalyst is recycled 5 times, and the removal rate of tetracycline can be maintained at more than 80%. Different actual water bodies do not have a significant effect on the oxidation system of the magnetic ferroferric oxide biochar, indicating that the system has good practical application capabilities. In addition, the system has a strong degradation effect on a variety of organic pollutants, among which the degradation effect on methylene blue is the best, indicating that it has good applicability in complex water environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Flow chart of preparing OBC and Fe3O4@OBC in Example 1;
[0024] Figure 2 SEM images of OBC and Fe3O4@OBC prepared in Example 1;
[0025] Figure 3 The nitrogen adsorption-desorption curve and pore size distribution diagram of Fe3O4@OBC prepared in Example 1 (inner figure);
[0026] Figure 4 Magnetic hysteresis loop (VSM) and magnetic separation diagram of Fe3O4 and Fe3O4@OBC prepared in Example 1;
[0027] Figure 5FT-IR images of OBC, Fe3O4 and Fe3O4@OBC prepared in Example 1;
[0028] Figure 6 XRD patterns of OBC and Fe3O4@OBC prepared in Example 1;
[0029] Figure 7 This is the degradation effect diagram of tetracycline (TC) by different oxidation systems;
[0030] Figure 8 This is a diagram showing the effect of the Fe3O4@OBC system prepared in Example 1 on the degradation efficiency of tetracycline (TC) under different conditions;
[0031] Fig. 9 This is a graph showing the effect of anions and humic acid (HA) on the degradation efficiency of tetracycline (TC) in the Fe3O4@OBC system prepared in Example 1;
[0032] Fig.10 This is a diagram showing the effect of different actual water bodies and different pollutants on the degradation of tetracycline (TC) by the Fe3O4@OBC system prepared in Example 1;
[0033] Fig.11 The cycle experiment of TC degradation by the Fe3O4@OBC system prepared in Example 1, the Fe ion leaching concentration, and the FT-IR and XRD patterns before and after the reaction;
[0034] Fig.12 This is the EPR spectrum analysis diagram of the Fe3O4@OBC system prepared in Example 1;
[0035] Fig.13 This is the XPS graph of Fe3O4@OBC prepared in Example 1 before and after the reaction. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing magnetic ferroferric oxide biochar, comprising the following steps:
[0037] After calcining the peel powder in a nitrogen protective atmosphere, the peel powder is crushed and sieved in sequence to obtain nitrogen-containing peel biochar;
[0038] The nitrogen-containing peel biochar, organic solvent, iron salt and sodium acetate are mixed and subjected to a solvothermal reaction to obtain magnetic ferrosoferric oxide biochar.
[0039] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0040] The present invention calcines the peel powder in nitrogen protective gas, and then pulverizes and sieves the powder in sequence to obtain nitrogen-containing peel biochar.
[0041] As an embodiment, the fruit peel powder includes one or more of orange peel powder, tangerine peel powder and grapefruit peel powder, and in a specific embodiment, it is orange peel powder.
[0042] As an embodiment, the preparation method of the peel powder comprises the following steps: drying the peel to constant weight, crushing and sieving in sequence, and storing in a vacuum for standby; the drying temperature is 65 to 80°C, and the time is 24 to 72 hours; the crushing is grinding; and the sieving is performed using a 50-mesh sieve. In a specific embodiment, the orange peel is the peel of Gannan navel orange; the drying temperature is 65°C, and the time is 72 hours. The orange peel used in the present invention is the Gannan navel orange peel from Ganzhou City, Jiangxi Province. Compared with the composting process of peel waste, it is more efficient to prepare it into biochar to treat antibiotic-contaminated wastewater.
[0043] As an embodiment, the calcination temperature is 500-800°C, the holding time is 2-3h; the heating rate of the temperature to the calcination temperature is 5-10°C / min; the crushing is grinding; the screening is performed with a 100-mesh sieve; after the screening, it also includes: washing and drying the sieved material after the screening in sequence; the washing is repeatedly rinsed with ethanol and deionized water in sequence; the number of washings is 2-3 times; the drying temperature is 65-80°C; the drying is to constant weight. In a specific embodiment, the calcination temperature is 600°C, the holding time is 2h; the heating rate of the temperature to the calcination temperature is 10°C / min; the number of washings is 3 times; the drying temperature is 65°C.
[0044] The peel biochar provided by the present invention contains nitrogen, and the nitrogen can increase the electronegativity of the biochar, which is beneficial to electron transfer, thereby improving the ability of the magnetic ferroferric oxide biochar to act as a catalyst to catalyze the oxidant to degrade organic pollutants.
[0045] After obtaining the nitrogen-containing peel biochar, the present invention mixes the nitrogen-containing peel biochar, an organic solvent, an iron salt and sodium acetate, and performs a solvothermal reaction to obtain magnetic ferrosoferric oxide biochar.
[0046] As an embodiment, the iron salt is ferric chloride; the organic solvent is ethylene glycol; the ratio of the mass of the nitrogen-containing peel biochar to the volume of the organic solvent is 1g:100-150mL; the mass ratio of the nitrogen-containing peel biochar to the iron salt is 1:3-5; the mass ratio of the nitrogen-containing peel biochar to sodium acetate is 1:3-5. In a specific embodiment, the iron salt is ferric chloride hexahydrate; the ratio of the mass of the nitrogen-containing peel biochar to the volume of the organic solvent is 0.3g:30mL; the mass ratio of the nitrogen-containing peel biochar to the iron salt is 0.3:1.25; the mass ratio of the nitrogen-containing peel biochar to sodium acetate is 0.3:1.32.
[0047] As an implementation mode, the nitrogen-containing peel biochar, organic solvent, iron salt and sodium acetate are mixed as follows: after the nitrogen-containing peel biochar and organic solvent are mixed by ultrasound, iron salt and sodium acetate are added for stirring; the power of the ultrasound is 200-300W; the time of the ultrasound is 2-4h; the stirring rate is 300-400rpm; the stirring time is 20-40min. In a specific embodiment, the power of the ultrasound is 200W; the time of the ultrasound is 2h; the stirring rate is 300rpm; the stirring time is 30min.
[0048] As an implementation mode, the temperature of the solvothermal reaction is 150-300°C, and the holding time is 6-12 hours. In a specific embodiment, the temperature of the solvothermal reaction is 200°C, and the holding time is 10 hours.
[0049] As an embodiment, after the solvothermal reaction, the method further comprises: separating the solid-liquid of the product of the solvothermal reaction, washing the obtained black precipitate and drying it to constant weight; the washing is repeatedly rinsed with ethanol and deionized water in sequence; the drying temperature is 65 to 80° C., and the drying is performed to constant weight. In a specific embodiment, the drying temperature is 60° C.
[0050] Figure 1 This is a flow chart for preparing OBC and Fe3O4@OBC in Example 1. After the orange peel powder is dried, the temperature is increased to 600°C at 10°C / min in a nitrogen protective atmosphere and calcined for 2 hours to obtain nitrogen-containing peel biochar, which is then mixed with ethylene glycol and ultrasonically treated for 2 hours. Sodium acetate and ferric chloride hexahydrate are added and stirred for 30 minutes. The solvent thermal reaction is carried out at 200°C for 10 hours, and the solid-liquid separation is performed to obtain magnetic ferrosoferric oxide biochar (Fe3O4@OBC).
[0051] The present invention also provides magnetic ferroferric oxide biochar prepared by the preparation method described in the above technical scheme, comprising nitrogen-containing peel biochar and ferroferric oxide loaded on the surface and pores of the nitrogen-containing peel biochar; the mass percentage of ferroferric oxide in the magnetic ferroferric oxide biochar is 18-30%, the mass percentage of nitrogen-containing peel biochar is 65-81%, and the mass percentage of nitrogen element is 1-5%; the specific surface area of the magnetic ferroferric oxide biochar is 20-40m 2 / g, pore volume is 0.0030~0.0040cm 3 / g, pore size is 2~30nm.
[0052] As an implementation mode, the mass percentage of ferroferric oxide in the magnetic ferroferric oxide biochar is 20-25%, the mass percentage of nitrogen-containing peel biochar is 70-75%, and the mass percentage of nitrogen is 2-5%; the specific surface area of the magnetic ferroferric oxide biochar is 25-35m 2 / g, pore volume is 0.0030~0.0035cm 3 / g, pore size is 5~20nm.
[0053] The present invention also provides the use of the magnetic ferroferric oxide biochar described in the above technical solution as a catalyst in degrading organic pollutants.
[0054] The present invention also provides a method for degrading organic pollutants, comprising the following steps:
[0055] A medium containing organic pollutants, peracetic acid and a catalyst are mixed to perform degradation treatment;
[0056] The catalyst is the magnetic ferroferric oxide biochar described in the above technical solution.
[0057] As an embodiment, the organic pollutant is one or more of tetracycline (TC), bisphenol A (BPA), methylene blue (MB), sulfamethoxazole (SMX), diclofenac (DCF) and ofloxacin (OFLX), and in a specific embodiment, it is tetracycline or methylene blue; the concentration of the organic pollutant in the medium containing organic pollutants is 5 to 20 mg / L, and in a specific embodiment, it is 10 mg / L; the medium is water
[0058] As an implementation mode, the dosage of the catalyst in the medium containing organic pollutants is 0.02-0.10 g / L, and in a specific embodiment, it is 0.06 g / L.
[0059] As an embodiment, the concentration of the peracetic acid in the medium containing organic pollutants is 25-200 μmol / L, and in a specific embodiment, it is 200 μmol / L.
[0060] As an embodiment, the pH value of the mixed system obtained by mixing the antibiotic-containing medium, peracetic acid and catalyst is 2-11, as another embodiment, it is 3-9, and in a specific example, it is 3-7.
[0061] As an embodiment, the preparation method of peracetic acid comprises the following steps: mixing acetic acid and hydrogen peroxide, adding sulfuric acid to the obtained mixture and stirring, refrigerating and standing in a brown wire-mouth bottle, and measuring the concentration of the obtained solution after it stabilizes; the volume ratio of the acetic acid and hydrogen peroxide is 3:2; the volume ratio of the acetic acid and sulfuric acid is 15:1; the mass concentration of the sulfuric acid is 98%; the mass concentration of the hydrogen peroxide is 28-30%, and is 30% in a specific embodiment; the stirring temperature is 20-30°C; the stirring rate is 200-300rpm, and is 300rpm in a specific embodiment; the stirring time is 20-40min, and is 30min in a specific embodiment; the refrigerated standing temperature is 2-8°C, and is 4°C in a specific embodiment, and the time is 6h.
[0062] Peracetic acid (PAA) is more advantageous than hydrogen peroxide as an oxidant for advanced oxidation techniques (AOPs). As a peroxide similar to hydrogen peroxide, PAA's lowest unoccupied molecular orbital energy (-0.25 eV) is lower than hydrogen peroxide (0.57 eV), and the peroxide bond energy of PAA (159.1 kJ / mol) is much lower than hydrogen peroxide (213.5 kJ / mol), all of which indicate that PAA is more easily activated. In addition, hydrogen peroxide belongs to Fenton and is only effective under acidic conditions, and the oxidizing ability of hydrogen peroxide is not as strong as that of peracetic acid.
[0063] As an implementation mode, the mixing and degradation treatment of the medium containing organic pollutants, peracetic acid and catalyst are all carried out under light-proof conditions.
[0064] As an embodiment, the temperature of the degradation treatment is 20-30°C, and in a specific embodiment, it is 25°C; the degradation treatment is carried out under shaking conditions; the shaking rate is 150-250rpm, and in a specific embodiment, it is 200rpm; the degradation treatment time is 5-30min, and in a specific embodiment, it is 30min.
[0065] As an embodiment, after the degradation treatment, the method further comprises: recovering the catalyst after the degradation treatment from the mixture after the degradation treatment to obtain recovered magnetic ferroferric oxide biochar; the recovery method comprises: when the medium is water, solid-liquid separation. The present invention has no special limitation on the recovery method, and any recovery method known in the art can be used.
[0066] As an embodiment, the recovered magnetic ferrosoferric oxide biochar is recycled; the number of recycling times is at least 5 times.
[0067] As an implementation mode, the removal rate of the organic pollutants is ≥80%.
[0068] The magnetic ferroferric oxide biochar provided by the present invention is used as a catalyst to effectively improve the ability to produce advanced oxidation active species when activating peracetic acid (PAA). During the reaction, the magnetic ferroferric oxide biochar catalyst activates peracetic acid to produce organic free radicals (CH3C(O)O· and CH3C(O)OO·), hydroxyl groups and singlet oxygen to degrade organic pollutants in wastewater. Compared with the carbon material coupled peracetic acid system reported in recent years, the magnetic ferroferric oxide biochar / peracetic acid system (Fe3O4@OBC / PAA) in the present invention has higher stability and can maintain high catalytic efficiency during multiple recycling processes, providing a feasible solution for developing a highly stable, easily recyclable and green peracetic acid advanced oxidation system. The method has a wide range of applicability to the pH value of wastewater and has excellent degradation performance for organic pollutant wastewater with a pH value of 2 to 11. Therefore, in practical applications, the magnetic ferroferric oxide biochar can be recycled and wastewater treatment can be carried out within a wide pH range, thereby saving catalyst costs and reagent costs for adjusting the pH value of wastewater. Moreover, different actual water bodies did not have a significant impact on the oxidation system, indicating that the system has good practical application capabilities. In addition, the system has a strong degradation effect on a variety of organic pollutants (especially methylene blue), indicating that the Fe3O4@OBC / PAA system has good applicability in complex water environments.
[0069] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0070] Example 1
[0071] The preparation of magnetic ferroferric oxide biochar specifically includes the following steps:
[0072] The peel of Gannan navel orange is used as raw material, dried at 60℃ to constant weight, ground through a 50-mesh sieve, and the obtained orange peel powder is vacuum stored for later use;
[0073] The orange peel powder was heated to 600°C at a heating rate of 10°C / min under N2 protection and calcined for 2 hours, then ground through a 100-mesh sieve after cooling, and then repeatedly rinsed with ethanol and deionized water for 3 times, and then dried at 65°C to constant weight to obtain nitrogen-containing orange peel biochar (OBC for short);
[0074] 0.3 g nitrogen-containing orange peel biochar was mixed with 30 mL ethylene glycol and ultrasonically treated at 200 W for 2 h. Then 1.25 g ferric chloride hexahydrate and 1.32 g sodium acetate were added to the above solution and stirred at 300 rpm for 30 min. The mixed solution was transferred to a reactor and subjected to solvothermal reaction at 200 °C for 10 h. The black precipitate separated from the solid and liquid was repeatedly rinsed with ethanol and deionized water, and then dried at 60 °C to constant weight to obtain magnetic ferrosoferric oxide biochar (Fe3O4@OBC for short).
[0075] Comparative Example 1
[0076] The nitrogen-containing orange peel biochar (OBC for short) prepared in Example 1 was used as a comparative example.
[0077] Comparative Example 2
[0078] The ferroferric oxide (Fe3O4) prepared by the steps of Example 1 is used as a comparative example.
[0079] Application Example 1
[0080] The preparation of Peracetic Acid specifically comprises the following steps:
[0081] Mix 60 mL of CH3COOH and 40 mL of 30% H2O2 in a 250 mL beaker, then add 4 mL of concentrated sulfuric acid (98%) and stir at 300 rpm for 30 min. Store the mixture in a 250 mL brown thread bottle and place it in a 4°C refrigerator for 6 h. Measure the concentration after the solution stabilizes.
[0082] To 50 mL of an aqueous solution containing tetracycline (tetracycline concentration of 10 mg / L), 100 μmol / L of peracetic acid and 0.06 g / L of the magnetic ferroferric oxide biochar catalyst prepared in Example 1 were added, and the pH value of the resulting mixed solution was adjusted to 5. The degradation treatment was carried out at 200 rpm in a 25°C constant temperature shaker under light-proof conditions for 30 min, and the solid-liquid separation was performed to obtain treated sewage and recovered magnetic ferroferric oxide biochar, respectively.
[0083] Comparative application example 1
[0084] The difference from Application Example 1 is that peracetic acid is removed, and the magnetic ferroferric oxide biochar catalyst prepared in Example 1 is replaced by the nitrogen-containing orange peel biochar (OBC for short) in Comparative Example 1.
[0085] Comparative Application Example 2
[0086] The difference from Application Example 1 is that peracetic acid is removed and only the magnetic ferrosoferric oxide biochar catalyst prepared in Example 1 is used.
[0087] Comparative Application Example 3
[0088] The difference from Application Example 1 is that the magnetic ferroferric oxide biochar catalyst prepared in Example 1 is removed and only peracetic acid is used.
[0089] Comparative Application Example 4
[0090] The difference from Application Example 1 is that no catalyst is used, and only hydrogen peroxide is used.
[0091] Comparative Application Example 5
[0092] The difference from Application Example 1 is that peracetic acid is replaced by hydrogen peroxide.
[0093] Comparative Application Example 6
[0094] The difference from Application Example 1 is that the magnetic ferroferric oxide biochar catalyst prepared in Example 1 is replaced by the nitrogen-containing orange peel biochar (OBC for short) in Comparative Example 1.
[0095] Performance Testing
[0096] (1) Figure 2 These are SEM images of OBC and Fe3O4@OBC prepared in Example 1, where (a) and (b) are SEM images of OBC, (c) and (d) are SEM images of Fe3O4@OBC, (e) is the element mapping diagram of Fe3O4@OBC, and (f) is the element distribution diagram of Fe3O4@OBC.
[0097] from Figure 2 As can be seen from (a and b), a significant porous structure with large pore size and sufficient pores can be observed in OBC. Figure 2 (c and d) are nitrogen-containing orange peel biochar loaded with Fe3O4 (Fe3O4@OBC). It can be seen that the Fe3O4 nanoparticle clusters are not only distributed on the surface but also attached to the pores on the porous biochar structure. The agglomeration problem of Fe3O4 can be improved to a certain extent by loading biochar. The corresponding EDS spectra are shown in Figure 2. Figure 2 As shown in (e), the signals of C, O, N, Fe, and other elements were observed, among which C and O accounted for a larger proportion, which was mainly caused by the carbon skeleton of the biochar material and the oxygen element in each component. Figure 2 (f) It can be seen that the elements are evenly distributed on the surface of the catalyst, which indicates that Fe3O4@OBC is successfully prepared.
[0098] (2) Figure 3 This is the nitrogen adsorption-desorption curve and pore size distribution diagram of Fe3O4@OBC prepared in Example 1 (inner figure).
[0099] from Figure 3It can be seen that the N2 adsorption-desorption isotherm of the catalyst is a typical type IV isotherm. Combined with the pore size distribution diagram of Fe3O4@OBC, the pore size is mainly distributed in the range of 2 to 30 nm, which indicates that the material has a mesoporous structure with a narrow pore size distribution, and the size is uniform and spherical, which is consistent with the SEM characterization structure.
[0100] (3) Figure 4 Magnetic hysteresis loop (VSM) and magnetic separation diagram of Fe3O4 and Fe3O4@OBC prepared in Example 1.
[0101] from Figure 4 It can be seen that the magnetization curves of pure Fe3O4 and Fe3O4@OBC samples are symmetrical S-shaped, which means that the samples have superparamagnetism. The saturation magnetization values of Fe3O4 and Fe3O4@OBC were measured to be 79.57 and 43.40emu / g, respectively, indicating that the saturation magnetization value of Fe3O4@OBC has decreased, which is due to the presence of non-magnetic biochar carriers. However, as shown in the inset, under an external magnetic field, the Fe3O4@OBC material can achieve solid-liquid separation within 30s, indicating that the decrease in magnetic susceptibility does not affect the magnetic separation effect. The above results show that Fe3O4@OBC is a highly magnetic and recyclable catalyst that can also prevent secondary pollution of water bodies.
[0102] (4) Figure 5 FT-IR graphs of OBC, Fe3O4 and Fe3O4@OBC prepared in Example 1.
[0103] The present invention performs Fourier transform infrared spectroscopy analysis on OBC, Fe3O4 and Fe3O4@OBC materials to understand the possible functional groups. Figure 5 It can be seen that at 3424-3436, 1615-1631 and 1027-1034cm -1 The characteristic absorption peaks at 583.1 cm-1 can be attributed to the stretching vibrations of OH, C=C and CO, respectively. -1 The characteristic peak at 583.1 cm-1 can be attributed to the Fe-O stretching vibration of iron oxide, which is consistent with the peak at 583.1 cm-1 of Fe3O4. -1 In addition, the metal content in the material is reduced by loading OBC, resulting in a higher Fe3O4@OBC content at 583cm compared to Fe3O4. -1 The peak intensity representing the bond formation between metal ions and oxygen decreased. All the above results indicate that the synthesis of Fe3O4@OBC is successful.
[0104] (5) Figure 6 XRD patterns of OBC and Fe3O4@OBC prepared in Example 1.
[0105] The present invention analyzes the crystallinity of the catalyst by X-ray diffraction (XRD). Figure 6 It can be seen that the characteristic diffraction peaks of OBC appear at 2θ=25.0° and 44.0°, corresponding to the (002) crystal plane of disordered graphite and the (100) crystal plane of crystalline graphite structure, respectively. In addition, the magnetic Fe3O4@OBC has diffraction peaks at 2θ=18.3°, 30.1°, 35.5°, 43.0°, 53.4°, 57.0°, 62.5°, 70.9°, 73.9° and 78.9°, corresponding to the (111), (220), (311), (400), (422), (333), (440), (620)(533) and (444) crystal plane diffraction peaks of Fe3O4 (JCPDSNO.79-0418), respectively, which indicates that Fe3O4@OBC has been successfully prepared.
[0106] (6) Figure 7 This is a diagram showing the degradation effect of different oxidation systems on tetracycline (TC).
[0107] All experiments were carried out in a 50 mL conical flask, the reaction temperature was controlled at 25 ° C, and the reaction was protected from light. The reaction was carried out by adding peracetic acid (PAA), H2O2, Fe3O4@OBC or OBC prepared in Example 1 and 50 mL 10mg / L TC solution was mixed and stirred at 200rpm in a constant temperature shaking box during the reaction. Samples were taken out at regular intervals, quenched by adding excess Na2S2O3, and 1.5mL of liquid sample was collected by 0.22μm polyethersulfone membrane filtration. The concentration of the sample was determined by high performance liquid chromatography, wherein the injection volume was 10μL, the flow rate was 1mL / min, the chromatographic column was WYNP-C18 (4.6mm×250mm, 5μm), the column oven temperature was 30°C, the mobile phase was methanol (20% volume fraction), acetonitrile (10% volume fraction), 0.01mol / L oxalic acid solution (70% volume fraction), the UV detector wavelength was 355nm, the retention time (RT) was 7min, and 0.1mol / LNaOH and 0.1mol / L H2SO4 was used to adjust the initial pH (3-11), and all experiments were repeated at least twice. The degradation / adsorption effects of different systems on tetracycline included seven different systems: PAA alone, OBC alone, H2O2 alone, Fe3O4@OBC alone, OBC / PAA, Fe3O4@OBC / H2O2, and Fe3O4@OBC / PAA.
[0108] Depend on Figure 7It can be seen that the degradation efficiency of TC by OBC, Fe3O4@OBC, H2O2, and PAA alone within 30 minutes is low, indicating that the adsorption of OBC and Fe3O4@OBC, and the oxidation of H2O2 and PAA cannot achieve the degradation of TC. At the same time, the OBC / PAA system can only achieve a degradation efficiency of 30%, indicating that the activation effect of OBC on PAA is not obvious. The Fe3O4@OBC / PAA system can remove 95.8% of TC within 30 minutes, indicating that Fe3O4@OBC can effectively activate PAA to produce active species to degrade TC. In addition, since the PAA solution contains both PAA and H2O2, the degradation effect of the Fe3O4@OBC / H2O2 system on TC is also investigated. As shown in the figure, the degradation of TC by the Fe3O4@OBC / H2O2 system is only 21.0%, indicating that the H2O2 in the Fe3O4@OBC / H2O2 system hardly participates in the degradation of TC. (The experiment was conducted under the experimental conditions of 10 mg / LTC, 0.06 g / L catalyst, and 100 μmol / LPAA to determine the removal efficiency of the target pollutant TC at different time periods.)
[0109] (7) Figure 8 The effect of the Fe3O4@OBC system prepared in Example 1 on the degradation efficiency of tetracycline (TC) under different conditions, where (a) is the amount of catalyst, (b) is the amount of oxidant, and (c) is the initial pH.
[0110] When discussing the effects of catalyst dosage, PAA dosage, and solution pH on the TC degradation efficiency of Fe3O4@OBC / PAA. The dosage of Fe3O4@OBC / PAA, PAA dosage, and pH were replaced according to the following instructions: (1) Fe3O4@OBC / PAA dosage: 0.02, 0.04, 0.06, 0.08, 0.10 g / L; (2) PAA dosage was set to: 25, 50, 100, 150, 200 μmol / L; (3) pH was set to: 3, 5, 7, 9, 10. Repeat the above operations and measure the concentration of pollutants in each time period. The results are shown in the figure. Figure 8 As shown, the optimal conditions for the dosage of Fe3O4@OBC / PAA and the dosage of PAA during the reaction process are 0.06g / L catalyst and 100μmol / L PAA, respectively. The degradation effect of TC within 30 minutes reached 95.8%. The results also show that the degradation ability of the Fe3O4@OBC / PAA system is not affected in the pH range of 3 to 7. However, when the pH value is 9 and 11, the degradation efficiency of TC drops to 79.4% and 55.1%, respectively. In other words, acidic conditions are conducive to the degradation of TC.
[0111] (8) Fig. 9The effects of anions and humic acid (HA) on the degradation efficiency of tetracycline (TC) in the Fe3O4@OBC system, where (a~c) are anions (Cl - 、HCO3 - 、H2PO4 - ), (d) is HA.
[0112] When studying the effects of anions and humic acid on the TC degradation efficiency of Fe3O4@OBC / PAA, the following description was used to analyze the anions (Cl - 、HCO3 - 、H2PO4 - ) and humic acid (HA) addition were tested: (1) Cl - 、HCO3 - 、H2PO4 - The concentration of HA in the solution is 0, 0.2, 0.5, 1, and 2 mmol / L; (2) the concentration of HA in the solution is 1, 2, 5, and 10 mg / L. Repeat the above operation and measure the concentration of the pollutant in each time period. The results are as follows: Fig. 9 As shown, the anion (H2PO4 - >HCO3 - >Cl - ) and humic acid (HA) have different degrees of inhibitory effect on TC.
[0113] (9) Fig.10 The effects of different actual water bodies and different pollutants on the degradation of tetracycline (TC) by the Fe3O4@OBC system prepared in Example 1, where (a) represents different pollutants and (b) represents different actual water bodies.
[0114] In order to broaden the degradation efficiency of Fe3O4@OBC / PAA system on tetracycline in actual water bodies, the degradation of tetracycline in five different actual water bodies (deionized water (DW), Ganjiang raw water (GJW), Poyang Lake surface water (PYW), Wannian sewage treatment plant effluent (WNW), Gaoan booster station wastewater outlet effluent (GAW) and Fairy Lake surface water (FLW)) was compared, as well as the degradation of various organic pollutants (methylene blue, diclofenac, bisphenol A, sulfamethoxazole, ofloxacin) by Fe3O4@OBC / PAA system. The results are as follows Fig.10 As shown in (b), the degradation effect of the Fe3O4@OBC / PAA system in the Ganjiang raw water (GJW), Poyang Lake surface water (PYW), Wannian sewage treatment plant effluent (WNW), Gao'an booster station wastewater outlet effluent (GAW), and Fairy Lake surface water (FLW) was slightly reduced, but not significant, and the degradation rate was all above 80%. This may be due to the fact that under actual water environment conditions, some organic matter and inorganic anions inhibit the catalytic system, resulting in a decrease in the degradation efficiency of tetracycline.
[0115] from Fig.10 (a) It can be seen that the Fe3O4@OBC / PAA system showed good performance in the degradation of various organic pollutants (methylene blue (MB) 100% > diclofenac (DCF) 93.4% > bisphenol A (BPA) 92.1% > sulfamethoxazole (SMX) 87.0% > ofloxacin (OFLX) 81.7%).
[0116] (10) Fig.11 The cyclic experiment of TC degradation by the Fe3O4@OBC system prepared in Example 1, the Fe ion leaching concentration, the FT-IR and XRD patterns before and after the reaction, wherein (a) is the cyclic experiment of TC degradation by the Fe3O4@OBC system; (b) is the Fe ion leaching concentration of Fe3O4 and Fe3O4@OBC; (c) is the FT-IR comparison diagram before and after the reaction; (d) is the XRD comparison diagram before and after the reaction.
[0117] The reusability of Fe3O4@OBC is an important issue for its practical application. Therefore, the catalyst was reused for five times. Fig.11 As shown in (a), the removal of TC is still effective, and the degradation rate of TC can still reach 83.3% in the fifth time.
[0118] In addition, in order to evaluate the environmental friendliness and stability of the catalyst, the Fe ion concentration of the catalyst leached was measured in the filtrate after the reaction of the Fe3O4 / PAA and Fe3O4@OBC / PAA systems. Fig.11 As shown in (b), compared with the amount of iron ions precipitated by Fe3O4 / PAA alone (0.0564 mg / L), the iron ion leaching concentration in Fe3O4@OBC / PAA was reduced to 0.0311 mg / L, which indicates that anchoring metal nanoparticles with biochar materials as carriers can effectively reduce the precipitation of metal ions and reduce the harm to the environment.
[0119] pass Fig.11 (cd) FTIR analysis and XRD measurement show that there is no significant change in the functional groups and phase structure of Fe3O4@OBC before and after the reaction, which further indicates that the catalyst can still maintain high purity and stability after the reaction. Therefore, the magnetic Fe3O4@OBC material has good stability and broad application prospects.
[0120] (11) Fig.12 The EPR spectrum analysis diagram of the Fe3O4@OBC system prepared in Example 1, where (a) is TEMP as a capture agent 1O2; (b) is the EPR spectrum of OH· in the system with DMPO as the scavenger; (c) is CH3C(O)OO· in the ethanol system; (d) the effect of different quenchers on the oxidative degradation of TC in the Fe3O4@OBC / PAA system.
[0121] from Fig.12 It can be seen that by detecting possible reactive species through EPR, the characterization results show that there are three active substances, namely 1 O2, HO· and CH3C(O)OO·. To further explore the contribution of these active substances to TC degradation, quenching experiments were performed at an initial pH of 7. Tert-butyl alcohol (TBA) and furfuryl alcohol (FFA) are commonly used for OH· and 1 The quenchers of O2, methanol (MeOH) and 2,4-HD can remove OH· and RO· at the same time, and 2,4-HD is a very suitable quencher for removing peroxyl radicals. The results show that the removal rates of Fe3O4@OBC / PAA system in 30min are 91.08% and 88.60% after adding 20mmol / LTBA (tert-butyl alcohol) and FFA (furfuryl alcohol). This shows that OH· and 1 O2 is not the key active species for TC removal. When 20mmol / L methanol (MeOH) was added to the Fe3O4@OBC / PAA system, the removal rate of the pollutant decreased significantly. As the MeOH concentration increased to 50mmol / L, the inhibition effect became more obvious (25.48%). When 20mmol / L 2,4-HD (2,4-hexadiene) was added to the system, TC degradation was strongly inhibited, and the removal rate was only 12.14%. This indicates that RO·(CH3COO· and CH3C(O)OO·) are the main active species for TC degradation.
[0122] (12) Fig.13 XPS graphs of Fe3O4@OBC prepared in Example 1 before and after the reaction, where (a) is Survey, (b) is C1s, (c) is Fe 2p, and (d) is O1s.
[0123] To further investigate the activation mechanism of PAA, the surface chemical properties of the new and used Fe3O4@OBC composites prepared in Example 1 were characterized by XPS spectroscopy.
[0124] from Fig.13 From the XPS spectrum of Survey in (a), we can see that Fe, O and C elements exist in the material.
[0125] from Fig.13In the XPS spectrum of C1s in (b), peaks can be seen at binding energies of 284.80 eV, 286.26 eV, and 288.64 eV, representing CC, CO, and C=C, respectively. The binding energy and relative content of each carbon skeleton of Fe3O4@OBC before and after the reaction hardly changed, indicating that Fe3O4@OBC has good structural stability in activating PAA to degrade TC, which also confirms the potential ability of material recycling.
[0126] exist Fig.13 In (c), the XPS spectrum of Fe 2p has two main peaks at 711.18 eV and 724.08 eV, representing the 2P 3 / 2 and 2P 1 / 2 orbit, and the peaks at 718.58eV and 733.95eV are their satellite peaks. By further peak separation, it can be concluded that the form of Fe in the material is Fe 2+ and Fe 3+ . Fe before reaction 2+ and Fe 3+ The relative contents of Fe and Fe are 16.33% and 66.79% respectively. 2+ and Fe 3+ The relative content of Fe 3+ Converted to Fe 2+ It also shows that the Fe element participates in the reaction of Fe3O4@OBC in activating PAA to degrade TC.
[0127] exist Fig.13 In (d), the XPS spectrum of O 1s can be fitted into three peaks, among which the characteristic peak at the binding energy of 530.41 eV before the reaction corresponds to the lattice oxygen (O 2- ), the characteristic peak at 531.94 eV is attributed to the -OH or -COOH chemical bonds on the catalyst surface. After the reaction, the lattice oxygen (O 2- ) decreased from 54.27% to 50.22%, indicating that the active lattice oxygen released by the catalyst participated in the process of activating PAA to degrade TC. This is because H2O or O2 is transferred to the surface of the solid catalyst by adsorption, resulting in an increase in the adsorbed oxygen content on the catalyst surface. 2- The decrease in content can be attributed to the reduction of high-valent metals.
[0128] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing magnetic ferroferric oxide biochar, characterized in that: The following steps are involved: After calcining the peel powder in a nitrogen protective atmosphere, the peel powder is crushed and sieved in sequence to obtain nitrogen-containing peel biochar; The nitrogen-containing peel biochar, organic solvent, iron salt and sodium acetate are mixed and subjected to a solvothermal reaction to obtain magnetic ferrosoferric oxide biochar.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the nitrogen-containing peel biochar to the iron salt is 1:3-5; the mass ratio of the nitrogen-containing peel biochar to sodium acetate is 1:3-5.
3. The preparation method according to claim 1 or 2, characterized in that: The temperature of the solvent thermal reaction is 150-300° C., and the insulation time is 6-12 hours.
4. The magnetic ferroferric oxide biochar prepared by the preparation method according to any one of claims 1 to 3, characterized in that: The invention comprises nitrogen-containing peel biochar and ferroferric oxide loaded on the surface and pores of the nitrogen-containing peel biochar; the mass percentage of ferroferric oxide in the magnetic ferroferric oxide biochar is 18-30%, the mass percentage of the nitrogen-containing peel biochar is 65-81%, and the mass percentage of nitrogen element is 1-5%; the specific surface area of the magnetic ferroferric oxide biochar is 20-40 m 2 / g, pore volume is 0.0030~0.0040cm 3 / g, pore size is 2~30nm.
5. Use of the magnetic ferroferric oxide biochar as claimed in claim 4 as a catalyst in the degradation of organic pollutants.
6. A method for degrading organic pollutants, characterized in that: The following steps are involved: A medium containing organic pollutants, peracetic acid and a catalyst are mixed to perform degradation treatment; The catalyst is the magnetic ferroferric oxide biochar as described in claim 4.
7. The method according to claim 6, characterized in that The organic pollutants are one or more of tetracycline, bisphenol A, methylene blue, sulfamethoxazole, diclofenac and ofloxacin.
8. The method according to claim 6, characterized in that The concentration of organic pollutants in the medium containing organic pollutants is 5 to 20 mg / L.
9. The method according to claim 6, characterized in that The dosage of the catalyst in the medium containing organic pollutants is 0.02-0.10 g / L.
10. The method according to claim 6, characterized in that The concentration of the peracetic acid in the medium containing organic pollutants is 25-200 μmol / L.
